ANALISIS POSTUR KERJA TERHADAP KELUHAN MUSCULOSKELETAL PADA PEKERJA DI TEMPAT PENGASAPAN IKAN X KALI ASIN, KELURAHAN BANDARHARJO, KECAMATAN SEMARANG UTARA - Dhiny Sartika Larasandi; Suroto Suroto; Baju Widjasena (Jurnal Kesehatan Masyarakat (Undip), 2016)
Informal sector has high health risk, but it has not been touched by its owners to care about workers’ health. One of the risks that may occur is Musculoskeletal complaints, which is complaints on parts of the skeletal muscles that felt starting from very mild to very sick. Previous research on gold miners load transport workers in Cilograng in 2010 that 79,2 percent experienced Musculoskeletal complaints as result of their work. One aspect which is considered by ergonomic is working postures, which is various positions of the worker's body during work activities. Fish smoking is manual work with simple and traditional tools. Activities in fish smoking are at risk for MSDs because of the static and repetitive postures. The purpose of this study was to analyze the working posture towards Musculoskeletal complaints of workers at a fish smokehouse X Kali Asin, Bandarharjo village, District of North Semarang. This type of research is descriptive with qualitative approach. Seven workers of fish smokehouse X participated in this research. Triangulation tool in this study is the assessment of Rapid Entire Body Assessment (REBA) methods. The results showed 3,33 percent of medium risk; 46,67 percent of high risk; and 50 percent of very high posture. Complaints from workers are aches, cramps, tingling, stiffness, heat, and pain. All results of Musculoskeletal complaints that should be felt by workers are different from REBA assessment. It is caused by difference postures of the trunk, neck, legs, upper arms, lower arms, and wrists, and the actions taken to resolve the complaints. Workers should have the correct working posture and stretching to overcome the Musculoskeletal complaints.